Unique development of narratological approaches to the apocryphal or deuterocanonical books of the Septuagint with special emphasis on the North-West University scholarship - Jordaan, Pierre J. (HTS teologiese studies, 2021)
This article aims to present a brief historical overview of interpretative theories and methods relevant to those books that are included in either the Protestant Apocrypha or the Catholic Deuterocanonical in the LXX (Septuagint) for the period 1891–2020. The aim of the article is not to give a complete description of all research on apocryphal/deuterocanonical books. The author’s journey with the relevant literature commenced in 2006, when he was appointed as one of the translators of apocryphal texts for a new edition of the new Afrikaans Bible (2020). Initially, he felt trapped as if in a maze. However, as his research progressed and as he met and talked to LXX experts at that stage, the road began to seem less of an obstacle and more like a challenge. One of the important aspects that he discovered was that not every text in the LXX has a so-called Hebrew Vorlage. Although the author describes different approaches used to interpret LXX material, for example historical-grammatical methods, his focus is on South African LXX research that has made a unique contribution to the previous and existing research, especially by the researchers of the North-West University.Contribution: The article briefly discusses several researchers who have made unique contributions to the LXX apocryphal/deuterocanonical research during the last decade. These scholars utilised different methods to interpret the LXX texts – methods that were not previously employed regularly if at all, for example narratology and narrative theory, cognitive linguistics, cultural anthropology, semiotic theory, rhetorical theory and performance theory.